Flexural Strength Prediction of Welded Flange Plate Connections Based on Slenderness Ratios of Beam Elements Using ANN - Amir A. Hedayat; Ehsan Jazebi; Saman AsadAbadi; Amin Iranpour (Advances in Civil Engineering)
The present study was aimed to investigate the strength and ductility of welded flange plate (WFP) connections. Using the FE method, 52 WFP connections with different beam overall depths and beam flanges/web slenderness ratios were analyzed. Fragility curves indicated that, for a WFP connection which is designed based on the seismic codes, its strength is of more concern than its ductility. In addition, limiting the width-to-thickness ratios of the beam flanges and web plates to 0.3E/fy and 2.45E/fy, respectively, may not always lead to the achievement of adequate connection’s strength and ductility. Proposed theoretical formulas and artificial neural network- (ANN-) based models developed in this study were able to adequately predict the connection strength.